Generalized pseudoconvex functions and multiobjective programming - Mukherjee, R.N. (My University, 1997)
In a recent work, cited in the Introduction, a concept of generalized pseudoconvexity was used to obtain optimality results in nonlinear programming. In the present work we give sufficient optimality conditions, in the context of the multiobjective programming problem under the assumptions of generalized pseudoconvexity on objective and constraint functions. An application of such a result is given for fractional programming also.
Keywords: Constraint theory; Functions; Optimization; Problem solving; Fractional programming; Generalized pseudoconvex functions; Multiobjective programming; Nonlinear programming